Manajemen Merek Strategis pada Perguruan Tinggi: Studi Empirik Bauran Pemasaran di Universitas Terbuka - Milde Wahyu; Mellya Embun Baining; Syahmardi Yakop (Ekonomis: Journal of Economics and Business, 2023)
Intense competition among universities for new student enrollments has created a strong need for significant differentiation. This article introduces the concept of strategic brand management as a way to distinguish open distance education (in this case, Open University) and discusses how they strategically manage their brand through the higher education marketing mix (namely, prominence, prospectus, program, cost, staff, incentives, and promotion). Using a closed-ended survey and PLS-SEM modeling from a sample of management students, the research finds that utilitarian elements (namely, prominence, prospectus, program, and cost) in the higher education marketing mix have a direct positive impact on the university brand. However, hedonic elements (namely, staff, incentives, and promotion) in the higher education marketing mix do not have a significant impact. Implications of these findings for theory, practice, and future research directions are concluded.